INTERPERSONAL SKILL DALAM KAJIAN NEUROSAINS - Silvianetri Silvianetri (Alfuad: Jurnal Sosial Keagamaan, 2019)
The study of interpersonal skills in the of field of neuroscience aims to reveal the relevance of the development of brain function with patterns of interaction with others. Interpersonal skills are examined by neuroscience-based literature, both from books and journals. The study found that the most dominant brain area when interacting with others is the prefrontal cortex, which functions to regulate communication harmony, emotional regulation, empathy, morale and intuition. Based on these findings it can be concluded that if interpersonal skills run well, the brain in the prefrontal cortex's area will develop optimally. Conversely, if interactions with other people are disrupted, damage will occur in the┬á prefrontal cortex's area. This finding can be used as an initial discourse for counseling practitioners, psychologists, teachers, social workers or medical personnel for well being interpersonal skill client and patient .